Product Characteristics in International Economics Role and Impact on Economic Development - Huber, Stephan (Contributions to Economics,, 2018)
National economies are linked through flows of capital and goods. This book addresses those linkages, analyzes their benefits for economic development, and evaluates a country's opportunities to reap the best possible rewards by influencing the linkages. The book focuses on the role of product characteristics in international economics and their impact on economic development. After an introduction to the topic, it analyzes the influence of product sophistication on growth, and offers alternative means of measuring product characteristics. In turn, the book provides evidence for the impact of foreign equity on the characteristics of the products that firms produce. Moreover, it presents empirical findings that prove that the quality of a country's legal and institutional framework is influenced by said country's predisposition to trade rule-of-law-intensive goods.